Innovative Strategies for Pediatric Pain Management in Invasive Procedures: Role of Nursing and Non-Pharmacological Approaches - Obando , Alejandro; Pardal , María Antonieta (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: In recent years, several researches addressed the reduction of pain and anxiety in children undergoing invasive procedures, highlighting that pediatric pain management remains an infrequent practice, despite the availability of effective treatments. Studies such as those by Navarro (2013) and Cocerá Martínez (2016) highlighted the relevance of the role of Nursing in pain management and the need to implement non-pharmacological strategies, such as distraction methods, to relieve pain in pediatric patients. Development: Pain was defined as a subjective experience that combines sensory and emotional components. In the pediatric setting, its assessment represents a challenge due to the difficulty of young children to verbally express their sensations. Tools such as the Wong and Baker facial scale and the verbal numerical scale have facilitated the assessment of pain. In addition, non-pharmacological methods, such as the use of music, electronic games or relaxation techniques, proved to be effective in reducing pain perception and anxiety in children during procedures such as venipuncture. Prior preparation, through clear explanation of the procedure, also contributed to decrease stress in patients and their families. Conclusions: Adequate pain management in children requires a comprehensive approach combining pharmacologic and nonpharmacologic strategies. The active participation of the nursing professional, together with the implementation of innovative methods, is essential to improve the quality of pediatric care and promote a more humanized experience in health services